Negative electrode material and its manufacturing method, lithium ion battery
A lithium-oxygen controlled negative electrode material with a core and coating layer addresses the erosion and instability issues in silicon-oxygen materials, ensuring high initial efficiency and stable slurry processing.
Patent Information
- Application Number
- JP2024515337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-09-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-28
AI Technical Summary
Silicon-oxygen materials used as negative electrode materials in lithium ion batteries face issues with low initial coulombic efficiency due to exposure of internal Si crystal grains, leading to rapid erosion by water solvent and instability in aqueous slurry processing.
A negative electrode material with a controlled mass ratio of lithium to oxygen elements and a coating layer, where lithium is predominantly located in the core, reducing surface exposure and enhancing hydrophobicity to prevent solvent infiltration and improve stability.
The solution effectively reduces solvent erosion of Si crystal grains, enhances slurry processing stability, and maintains high initial efficiency and electrochemical properties by limiting lithium exposure on the surface.
Smart Images

Figure 2025501837000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to a Chinese patent application with application number 202211698602.X and title "Silicon-based negative electrode material, its manufacturing method and use" filed with the China Patent Office on December 28, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to the technical field of anode materials, in particular to anode materials, their manufacturing methods and applications. [Background technology]
[0003] Silicon-oxygen materials are used as negative electrode materials in lithium-ion batteries, and are characterized by their high specific capacity and good structural stability. The SiO x Lithiated framework SiO x , for example Li 2 SiO 3 , Li 2 S 2 O 5 etc., which can effectively solve the problem of low initial coulomb efficiency of silicon-oxygen materials.
[0004] However, if the silicon-oxygen material is subjected to the prelithiation treatment as it is, the silicon-oxygen material opens the pores to expose the internal Si crystal grains, and the surface of the material is filled with, for example, Li 2 SiO 3 , LiOH, Li 2 CO 3 It has a rich lithium-containing compound such as , and is extremely hydrophilic. During the manufacturing process of the aqueous slurry, the aqueous solvent easily infiltrates the prelithiated silicon oxide into the material, contacts the Si crystal grains, and accelerates the reaction with the Si crystal grains under alkaline conditions to produce a large amount of H 2 This destroys the stability of the slurry and significantly deteriorates the processing performance of the slurry.
[0005] In addition, the lithium-containing compounds abundant on the surface of the material are highly alkaline, which accelerates the erosion of the silicon crystal grains inside the silicon-oxygen material by the water solvent, while also corroding the slurry production equipment.
[0006] Therefore, there is an urgent need to use lithium silicon-oxygen raw materials, which have excellent electrochemical properties and good processing performance, as negative electrode materials. Summary of the Invention [Problem to be solved by the invention]
[0007] The objective of the present invention is to provide an anode material and a manufacturing method thereof, and a lithium ion battery, which significantly improve the stability of aqueous slurry processing under the premise that the anode material can guarantee the electrochemical properties of the material. [Means for solving the problem]
[0008] In a first aspect, the present invention provides an anode material, the anode material comprising a core and a coating layer located on at least a portion of a surface of the core, the core comprising a silicon-oxygen material, and the anode material comprising elemental lithium; When the mass ratio of lithium element to oxygen element in the negative electrode material is a, and when the negative electrode material is measured using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the mass ratio of lithium element to oxygen element in a region corresponding to information that can be detected in the process of detection by the photoelectron spectrometer from the surface of the negative electrode material toward the central region inside the negative electrode material is b, the relationship between a and b satisfies 0.4>a>b.
[0009] In some embodiments, the negative electrode material has at least one of the following characteristics (1) to (7): (1) the mass ratio a of lithium element to oxygen element in the negative electrode material satisfies 0.35>a>0.15; (2) the b satisfies 0.30>b>0.01; (3) when the negative electrode material is measured by an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the thickness of the region corresponding to information detectable by the photoelectron spectrometer in the process of detecting from the surface of the negative electrode material toward the central region inside the negative electrode material is 1 nm to 10 nm; (4) The silicon-oxygen material is SiO x 0 <x≦2である; (5) The silicon-oxygen material is Li 2 SiO 3 , Li 2 S 2 O 5 and Li 4 SiO 4 The lithium-containing compound includes at least one of the following: (6) When the mass of the negative electrode material is 100%, the mass ratio of the lithium element in the negative electrode material is 1 wt% to 15 wt%; (7) The molar ratio of Si element to O element in the negative electrode material is (0.8-1.2):1.
[0010] In some embodiments, the coating layer comprises a first coating layer and a second coating layer, the second coating layer being located between the core and the first coating layer and / or in areas of the surface of the core that are not covered by the first coating layer.
[0011] In some embodiments, the negative electrode material has at least one of the following characteristics (1) to (6): (1) The second coating layer includes at least one of a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide; (2) the material of the first coating layer includes a carbon material; (3) the mass ratio of the first coating layer to the negative electrode material is 0.1% to 5%; (4) the mass ratio of the second coating layer to the negative electrode material is 0.1% to 8%; (5) the thickness of the first coating layer is 1 nm to 1000 nm; (6) The thickness of the second coating layer is 1 nm to 1000 nm.
[0012] In some embodiments, the negative electrode material has at least one of the following characteristics (1) to (2): (1) The coating layer is a carbon layer; (2) The thickness of the coating layer is 1 nm to 1000 nm.
[0013] In some embodiments, the negative electrode material has at least one of the following characteristics (1) to (5): (1) The pore volume of the negative electrode material is less than 0.01 cm 3 / g; (2) The specific surface area of the negative electrode material is less than 4 m 2 / g; (3) When the contact angle θ of the negative electrode material with respect to acetone is measured by the Washburn method, θ > 20°; (4) The pH of the negative electrode material satisfies 7 < pH < 11.5; (5) The median diameter of the negative electrode material is 3.0 μm to 10.0 μm.
[0014] In a second aspect, an embodiment of the present application is a method for manufacturing a negative electrode material, comprising: a step of pre-lithiating a silicon oxygen raw material to obtain a pre-lithiated material containing lithium element and silicon oxygen raw material in a mass ratio of (0.02 to 0.16):1; a step of performing a first heat treatment on a mixture containing the pre-lithiated material and a polyvalent carboxylic acid to cure the mixture and obtain a precursor; a step of performing a second heat treatment on the precursor to carbonize the precursor and obtain a negative electrode material.
[0015] In some embodiments, the manufacturing method has at least one of the following characteristics (1) to (13): (1) The temperature of the first heat treatment is 150°C to 250°C; (2) The time of the first heat treatment is 5 h to 12 h; (3) the first heat treatment is performed in an air atmosphere; (4) before subjecting the mixture containing the prelithiated material and the polycarboxylic acid to a first heat treatment, the mixture containing the prelithiated material and the polycarboxylic acid is further subjected to a drying treatment; (5) The method further includes a step of drying the mixture containing the prelithiated material and the polycarboxylic acid before subjecting the mixture containing the prelithiated material and the polycarboxylic acid to a first heat treatment, and the temperature of the drying treatment is 45° C. to 90° C.; (6) performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into a solid-liquid mixture, and drying the material, thereby obtaining a precursor; (7) performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into solid and liquid, and drying the material, wherein a solvent used for the washing includes at least one of water and ethanol; (8) performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment, and drying the material, wherein the solid-liquid mass ratio during the washing is (1 to 4):1; (9) performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into solid and liquid, and drying the material, the washing time being 1h to 5h; (10) A process for performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into a solid-liquid mixture, and drying the material, the drying temperature being 80°C to 120°C; (11) The temperature of the second heat treatment is 500°C to 800°C; (12) The time of the second heat treatment is 5 hours to 12 hours; (13) The second heat treatment is carried out in a protective gas atmosphere.
[0016] In some embodiments, a method for preparing the mixture containing the prelithiated material and a polycarboxylic acid includes dissolving the polycarboxylic acid in a solvent to obtain a carbon source solution containing a polycarboxylic acid, and mixing the prelithiated material with the carbon source solution containing a polycarboxylic acid to obtain a mixture containing the prelithiated material and a polycarboxylic acid.
[0017] In some embodiments, the manufacturing method has at least one of the following characteristics (1) to (4): (1) The concentration of the carbon source solution is 3 mg / mL to 7 mg / mL; (2) The polycarboxylic acid includes at least one of citric acid, tartaric acid, maleic acid, trimesic acid, terephthalic acid, malic acid, and ethylenediaminetetraacetic acid; (3) the solvent comprises at least one of acetone, water, ethanol, methanol, isopropanol, dimethylformamide, toluene, and tetrahydrofuran; (4) The mass ratio of the prelithiated material to the polycarboxylic acid is (20 to 200:1).
[0018] In some embodiments, the silicon oxygen source is a silicon oxygen material having a coating layer, and the method for producing the silicon oxygen material having a coating layer includes providing a silicon oxygen material, mixing the silicon oxygen material with a coating material, and then performing a third heat treatment to obtain a silicon oxygen material having a coating layer.
[0019] In some embodiments, the manufacturing method has at least one of the following characteristics (1) to (4): (1) the mass ratio of the silicon-oxygen material to the coating material is 1:(0.005-0.05); (2) the coating material includes at least one of a carbon material, a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide; (3) The temperature of the third heat treatment is 500°C to 1000°C; (4) The time of the third heat treatment is 1 h to 6 h.
[0020] In some embodiments, pre-lithiation of the silicon oxygen material includes a step of performing a fourth heat treatment after mixing the silicon oxygen raw material and the lithium source to obtain a pre-lithiated material.
[0021] In some embodiments, the manufacturing method has at least one of the following characteristics (1) to (7): (1) The silicon oxygen raw material contains SiO y (0 < y ≤ 2); (2) The lithium source contains at least one of metallic lithium, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride, and lithium aluminum hydride; (3) The mass ratio of the silicon oxygen raw material to the lithium source is 100:(2 to 16); (4) The temperature of the fourth heat treatment is 100°C to 900°C; (5) The time of the fourth heat treatment is 1 h to 24 h; (6) The silicon oxygen raw material is a silicon oxygen material having a coating layer; (7) The silicon oxygen raw material is a silicon oxygen material having a coating layer, and the material of the coating layer contains at least one of a carbon material, a phosphate compound of silicon, a phosphate compound of aluminum, a phosphate compound of ammonium, and an aluminum phosphorus composite oxide.
[0022] In a third aspect, the present invention provides a lithium-ion battery including a negative electrode material manufactured by the manufacturing method of the negative electrode material described in the first aspect or the negative electrode material described in the second aspect.
Advantages of the Invention
[0023] The present invention has the following beneficial effects. In the present application, the mass ratio of lithium element to oxygen element in the negative electrode material is limited to a, and when the negative electrode material is measured by an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the mass ratio of lithium element to oxygen element in the region corresponding to the information detectable by the photoelectron spectrometer in the process from the surface of the negative electrode material to the central region inside the negative electrode material is b. The negative electrode material includes a core and a coating layer located on at least a part of the surface of the core, the core is mainly located in a region that cannot be detected by the X-ray photoelectron spectrometer with respect to the inside of the negative electrode material particle, and the mass of oxygen element in the negative electrode material is much larger than the mass of oxygen element in the region corresponding to the information detectable by the X-ray photoelectron spectrometer in the process from the surface of the negative electrode material to the central region inside the negative electrode material. Therefore, when a>b, it indicates that the relative content of lithium element in the surface layer of the negative electrode material of the present application is low, that is, the lithium element is mainly present in the region close to the inner center of the negative electrode material. In this way, in the process of processing and slurry preparation of the negative electrode material, the lithium element is mainly located in the central region inside the negative electrode material, so as to effectively reduce the water solvent molecules from entering the inside of the negative electrode material, reduce the erosion of the silicon crystal grains of the negative electrode material, and improve the stability of the negative electrode material in the slurry processing process. Here, the value of a is mainly related to the content of the lithium element in the core, and the higher the value of a, the higher the initial efficiency of the material, so the higher the a is, the more preferable it is. The lower the value of the material b, the more favorable it is for improving the hydrophobicity of the material, which makes it difficult for the water solvent to infiltrate and penetrate into the material, effectively blocking the contact between the Si crystal grains inside the material and the water solvent, and is favorable for improving the processing stability of the slurry, so the lower the b is, the more preferable it is. In this application, both a and b have upper limits, and when 0.4>a>b is satisfied, it can be ensured that the negative electrode material has high initial efficiency and good slurry processability. The content of lithium-containing compounds exposed on the surface of the product is reduced. [Brief description of the drawings]
[0024] In order to more clearly explain the technical solutions of the embodiments of the present invention, the following briefly introduces drawings necessary for the embodiments; obviously, the following drawings only show some embodiments of the present invention, so they should not be regarded as limiting the scope; those skilled in the art can obtain other related drawings based on these drawings without creative efforts. [Figure 1] FIG. 1 is a schematic diagram showing the configuration of a negative electrode material provided by the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing the configuration of the negative electrode material provided by the present invention. [Diagram 3] 1 is a flow chart of a method for producing a negative electrode material provided by the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the following will clearly and completely describe the technical solutions in the embodiments of the present invention. In the embodiments, unless specific conditions are specified, the procedures are carried out according to the general conditions or conditions provided by the manufacturers. For the reagents or equipment used, unless the manufacturers are specified, they are all conventional products obtained by commercial purchase.
[0026] In the prior art, after the carbon-coated silicon-oxygen material was prelithiated, voids were generated in the carbon layer, and the Li 2 S 2 O 5 , Li 2 SiO 3 etc. are exposed to H in the air 2 O, CO 2 etc. and Li 2 CO 3 , LiOH, and other lithium-containing compounds are formed, and the presence of these lithium-containing compounds makes the material sufficiently hydrophilic, so that water solvent molecules can easily infiltrate and erode the Si crystal grains inside the material during the slurry preparation process from the material. Therefore, reducing the exposure of the lithium-containing compounds in the material is the key to improving the slurry processability.
[0027] In view of this, an embodiment of the present invention provides a negative electrode material, which includes a core 100 and a coating layer 300 formed on at least a portion of the surface of the core 100, where the core 100 includes a silicon-oxygen material, and the negative electrode material includes a lithium element 200, as shown in FIG. When the mass ratio of lithium element 200 to oxygen element in the negative electrode material is a and when the negative electrode material is measured using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the mass ratio of lithium element 200 to oxygen element in a region corresponding to information detectable in the process of detection by the photoelectron spectrometer from the surface of the negative electrode material toward the central region inside the negative electrode material is b, the relationship between a and b satisfies 0.4>a>b.
[0028] In the above technical solution, the present application limits the mass ratio of lithium element to oxygen element in the negative electrode material to a, and when the negative electrode material is measured by an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the mass ratio of lithium element to oxygen element in the region corresponding to the information that can be detected by the photoelectron spectrometer in the process of detecting from the surface of the negative electrode material to the central region inside the negative electrode material is b. The negative electrode material includes a core and a coating layer located on at least a part of the surface of the core, the core is mainly located in the region that cannot be detected by the X-ray photoelectron spectrometer in the inside of the negative electrode material particle, and the mass of oxygen element in the negative electrode material is much larger than the mass of oxygen element in the region corresponding to the information that can be detected by the X-ray photoelectron spectrometer in the process of detecting from the surface of the negative electrode material to the central region inside the negative electrode material. Therefore, when a>b, it indicates that the relative content of lithium element in the surface layer of the negative electrode material of the present application is low, that is, the lithium element is mainly present in the region close to the inner center of the negative electrode material. In this way, in the process of processing and slurry preparation of the negative electrode material, the lithium element is mainly located in the central region inside the negative electrode material, so as to effectively reduce the water solvent molecules from entering the inside of the negative electrode material, reduce the erosion of the silicon crystal grains of the negative electrode material, and improve the stability of the negative electrode material in the slurry processing process. Here, the value of a is mainly related to the content of the lithium element in the core, and the higher the value of a, the higher the initial efficiency of the material, so the higher the a is, the more preferable it is. The lower the value of the material b, the more favorable it is for improving the hydrophobicity of the material, which makes it difficult for the water solvent to infiltrate and penetrate into the material, effectively blocking the contact between the Si crystal grains inside the material and the water solvent, and is favorable for improving the processing stability of the slurry, so the lower the b is, the more preferable it is. In this application, both a and b have upper limits, and when 0.4>a>b is satisfied, it can be ensured that the negative electrode material has high initial efficiency and good slurry processability. The content of lithium-containing compounds exposed on the surface of the product is reduced.
[0029] In this application, when the relationship between a and b satisfies a>b, it indicates that the content of lithium element in the negative electrode material is much greater than the content of lithium element in the second region.When a is greater than 0.4, that is, the doping degree of lithium element in the core is too large, the silicon crystal grains in the material grow abnormally, which is unfavorable to improving the cycle performance of the negative electrode material.
[0030] As shown in FIG. 2, the negative electrode material particles of the present application may be divided into two regions, that is, the negative electrode material particles of the present application have a first region 1 and a second region 2. The second region 2 is a region corresponding to information that can be detected by the X-ray photoelectron spectroscopy device (Thermo Scientific K-Alpha) in the process of detecting the negative electrode material from the surface of the negative electrode material toward the central region inside the negative electrode material when the negative electrode material is measured. The first region 1 is a region that cannot be detected by the X-ray photoelectron spectroscopy device with respect to the inside of the negative electrode material particle. In some embodiments, the first region 1 includes the core 100 and the partial coating layer 300 (shown in FIG. 2), and the second region 2 is another region of the negative electrode material other than the first region 1. In some other embodiments, the first region 1 includes the complete core 100 or the partial core 100, and the second region 2 is another region of the negative electrode material other than the first region 1. The present application does not specifically limit the specific boundary between the first region and the second region, and as can be understood, the region where the first region and the second region contact each other may be a region where there is a clear interface, such as an edge of a coating layer, or a region where there is a smooth transition without a clear interface.
[0031] In this application, the test methods for a and b are shown below. (1) The mass content of Li element in the whole negative electrode material is measured by using total melting ICP. Specifically, 0.500 g of the negative electrode material is placed in a clean platinum crucible, and then calcined at 750 ° C for 2 h in a muffle furnace in an air atmosphere to completely remove carbon elements; the calcined residue after cooling is dissolved in HNO 3The solution was thoroughly reacted with a mixture of 4 mL of HCl and 6 mL of HF, and then the platinum crucible containing the solution was placed on a 350 °C electric hotplate until the solvent was completely evaporated; after the crucible was cooled, another 6 mL of HCl was added and heated until the residue was completely dissolved, and the volume was quantified in a 100 mL plastic measuring flask; finally, the Li element content of the whole material was measured by an ICP spectrometer (Agilent 5800VDV ICP-OES).
[0032] (2) The mass content of the O element in the entire negative electrode material was measured using an ONH elemental analyzer (ONH-2000). Specifically, 10 mg to 13 mg of the negative electrode material was weighed and wrapped in nickel foil, and then the weight was transferred to the graphite crucible of the ONH elemental analyzer for measurement. The value of a was calculated from the above data.
[0033] (3) The mass contents of Li and O elements in the second region are measured by using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), and the operation steps are as follows: the negative electrode material of the present application is attached to a sample stage using double-sided carbon conductive adhesive or ordinary double-sided tape, and the sample stage with the negative electrode material is placed in an X-ray photoelectron spectrometer, the excitation source used in the X-ray photoelectron spectrometer is AlKα radiation, the beam spot is 400 μm, the pass energy of full spectrum scanning is 100 eV, and the step is 1 eV, and after obtaining the full spectrum scanning data, the Avantage software is used to read the full spectrum scanning data to obtain the contents of Li and O elements, and then the mass ratio b of Li and O elements is calculated and obtained.
[0034] In some embodiments, a satisfies 0.35>a>0.15. Specifically, provided that a>b is satisfied, the value of a may be 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, or 0.34, etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0035] In some embodiments, b satisfies 0.30 > b > 0.01. Specifically, the value of b may be, for example, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, or 0.28. Of course, other values within the above range are also possible, and the present application is not limited herein.
[0036] By controlling the ranges of the values of a and b within the above ranges, the stability of the slurry processing of the negative electrode material can be further improved. That is, no bubbles are generated in the produced slurry, and the slurry can be uniformly and flatly coated on the current collector during the coating process, and the negative electrode can exhibit better electrochemical characteristics.
[0037] In some embodiments, the silicon oxygen material contains silicon oxide SiO x and 0 < x ≤ 2. The silicon oxide contains oxygen atoms and silicon atoms, and the molar ratio of oxygen atoms to silicon atoms is 0 to 2, which is a silicon oxygen composite that does not contain 0. This may be a composite of two or more of Si, SiO 0.2 、SiO 0.5 、SiO 0.8 、SiO、SiO 1.2 、SiO 1.5 、SiO 1.8 or SiO 2 etc., or it may be a compound with the chemical formula SiO x . Of course, other values within the above range are also possible, and the present application is not limited herein.
[0038] In some embodiments, the lithium element in the negative electrode material exists in the form of a lithium-containing compound, and the lithium-containing compound includes at least one of Li 2 SiO 3 , Li 2 Si 2 O 5 and Li 4 SiO 4 , but is not limited thereto.
[0039] In some embodiments, when the mass of the negative electrode material is calculated as 100%, the mass ratio of lithium element in the negative electrode material is 1wt% to 15wt%, for example, it may be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0040] In some embodiments, the molar ratio of Si element to O element is (0.8-1.2):1. For example, it may be 0.8:1, 0.9:1, 1.0:1, 1.1:1 or 1.2:1, etc., and of course, it may be other values within the above range, and the present application is not limited thereto. The method for measuring the molar ratio of Si element to O element is as follows.
[0041] Use an ONH elemental analyzer to measure the content of all O elements in the material, use a carbon-sulfur analyzer to measure the content of all C elements in the material, use a total melting ICP to measure the content of all Li elements in the material, use a total melting ICP to measure the content of all impurity elements in the material, such as Fe, Mn, Ni, Cu, Mg, etc. impurities, and the rest of the material is the content of Si element by default. The Si / O molar ratio can be obtained by simply converting the O element content and the Si element content.
[0042] In some embodiments, the coating layer includes a first coating layer and a second coating layer, the second coating layer being located between the core and the first coating layer and / or in areas of the surface of the core that are not covered by the first coating layer.
[0043] In some embodiments, as shown in FIG. 1, the coating layer 300 includes a second coating layer 302 distributed on at least a portion of the surface of the core 100 and a first coating layer 301 distributed on at least a portion of the surface of the second coating layer 302.
[0044] In some embodiments, the material of the first coating layer 301 includes a carbon material.
[0045] In some embodiments, the second coating layer 302 includes at least one of a carbon material, a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide.
[0046] In some embodiments, the mass ratio of the first coating layer 301 in the negative electrode material is 0.1% to 5%. Specifically, it may be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0047] In some embodiments, the mass ratio of the second coating layer 302 in the negative electrode material is 0.1% to 8%. Specifically, it may be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0048] In some embodiments, the thickness of the first coating layer 301 is 1 nm to 1000 nm. Specifically, it may be 1 nm, 10 nm, 100 nm, 300 nm, 500 nm, 800 nm, 1000 nm, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0049] In some embodiments, the thickness of the second coating layer 302 is 1 nm to 1000 nm. Specifically, it may be 1 nm, 10 nm, 100 nm, 300 nm, 500 nm, 800 nm, 1000 nm, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0050] As can be understood, when the first coating layer 301 and the second coating layer 302 are made of the same material, the coating layer can be considered as a single layer structure, ie, the coating layer 300 is a carbon layer.
[0051] In some embodiments, the thickness of the coating layer 300 is 1 nm to 1000 nm, such as 1 nm, 50 nm, 100 nm, 300 nm, 500 nm, 700 nm, or 1000 nm, and of course, may be other values within the above range, and the present application is not limited thereto.
[0052] In some embodiments, the pore volume of the negative electrode material is less than 0.01 cm 3 / g. Specifically, it is less than 0.001 cm 3 / g, 0.003cm 3 / g, 0.005cm 3 / g, or 0.008 cm 3 / g, etc., and of course, other values within the above range are also acceptable, and the present application is not limited thereto. The pore volume of the negative electrode material of the present application is small, and the aqueous solvent is unlikely to infiltrate or penetrate into the material, and the contact between the Si crystal grains and the aqueous solvent inside the material is effectively blocked.
[0053] In some embodiments, the specific surface area of the negative electrode material is 4 m 2 / g. Specifically, it is less than 0.5m 2 / g, 1m 2 / g, 2m 2 / g or 3m 2 / g, etc., and of course may be other values within the above ranges, and the application is not limited thereto.
[0054] The pore volume and specific surface area of the negative electrode material are both parameters reflecting the outer surface of the negative electrode material, and the present application limits the pore volume and specific surface area to within the above ranges. It can be seen that the outermost surface of the negative electrode material of the present application is mainly a dense coating layer, which contributes to preventing penetration and erosion by the aqueous solvent during the production process of the slurry.
[0055] The pore volume is V, and the specific surface area is S, which can be measured by a conventional method, for example, the gas adsorption BET method. The adsorption gas used in the gas adsorption BET method is, for example, N 2 may be also possible.
[0056] In some embodiments, when the contact angle θ of the negative electrode material with respect to acetone is measured by the Washburn method, θ>20° is measured. Specifically, θ may be 25°, 30°, 35°, 40°, 45°, or 50°, etc. Of course, other values within the above range may also be possible, and this application is not limited here. Within the above limited range, it is shown that the negative electrode material of this application has good hydrophobicity. The lower the b value of the negative electrode material, the more advantageous it is for improving the hydrophobicity of the material. Thereby, it becomes difficult for the aqueous solvent to infiltrate and penetrate into the material, effectively blocking the contact between the Si crystal grains inside the material and the aqueous solvent, and it can be understood that it is advantageous for improving the processing stability of the slurry. Since the outermost surface of the negative electrode material is covered with a dense coating layer, the negative electrode material exhibits good hydrophobicity.
[0057] Note that the method for measuring the contact angle θ is as follows. The negative electrode material is filled into a glass tube having a filter at the bottom, brought into contact with the test liquid, and the increased mass and time in the tube are recorded after the rise of the test liquid ends, and the contact angle is calculated by the Washburn equation. During the measurement process, n-hexane was used as the test liquid, assuming the contact angle of n-hexane to be 0 degrees, the capillary constant after powder filling was measured, and then the powder was refilled by the same filling method, and the contact angle was measured with acetone.
[0058] In some embodiments, the pH value of the negative electrode material satisfies 7 < pH < 11.5. Specifically, pH may be 8, 8.5, 9, 9.5, 10, 10.5, 11, or 11.3, etc. Of course, other values within the above range may also be possible, and this application is not limited here. Within the above limited range, the low content of the lithium-containing compound on the surface of the negative electrode material of this application indicates that it is advantageous for alleviating the reaction between the aqueous solvent and the internal Si crystal grains and promoting the stability of the slurry. Also, corrosion of the slurry preparation apparatus can be avoided even at a low pH.
[0059] Note that the method for measuring the pH value of the negative electrode material is as follows. 5 g of the negative electrode material was ultrasonically dispersed in 45 g of water and then measured with a pH meter.
[0060] In some embodiments, the median diameter of the negative electrode material is 3.0 μm to 10.0 μm. Specifically, it may be 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, or 10.0 μm, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0061] In some embodiments, as shown in FIG. 3, the present application provides a method for preparing a negative electrode material, including the following steps: The silicon-oxygen raw material is prelithiated to obtain a prelithiated material, and the mass ratio of lithium element to silicon-oxygen raw material in the prelithiated material is (0.02-0.16):1; subjecting the mixture including the prelithiated material and the polycarboxylic acid to a first heat treatment to harden the mixture to obtain a precursor; The precursor is subjected to a second heat treatment to carbonize the precursor and obtain the negative electrode material.
[0062] In the above technical proposal, the present application uses polycarboxylic acid to carry out the first heat treatment coating treatment on the silicon oxygen raw material containing lithium element. Because the binding force between the polycarboxylic acid and the lithium-containing compound is strong, the polycarboxylic acid bonds with the lithium-containing compound to generate induced carbon, which tends to block the lithium-containing compound at a fixed point, rather than being randomly distributed on the surface of the silicon oxygen raw material. The generated induced carbon is mainly filled into the voids of the material, which serves to repair the voids that appear in the material after prelithiation. At the same time, the mass ratio of the lithium element to the silicon oxygen raw material in the prelithiation material is limited to (0.02-0.16):1, and the surface of the prelithiation material is further carbonized with polycarboxylic acid, so that the lithium element contained in the surface layer of the produced negative electrode material is reduced, and the negative electrode material shows 0.4>a>b. After that, the lithium-containing compound remaining on the material surface is removed by a washing operation, leaving a small amount of voids, and finally, the voids on the material surface are gradually reduced and closed by the high-temperature carbonization treatment of the second heat treatment, forming a dense carbon coating layer. As a result, in the process of processing the negative electrode material and preparing the slurry, the water solvent molecules can be effectively reduced from entering the inside of the negative electrode material, the erosion of the silicon crystal grains of the negative electrode material can be reduced, and the stability of the negative electrode material in the slurry processing process can be improved. The manufacturing method of the present application can improve the specific capacity, structural stability and initial efficiency of the material by pre-replenishing lithium through a pre-lithiation operation, and can efficiently block the lithium-containing compound at a fixed point by using a polycarboxylic acid as a carbon source. Because the binding ability between the polycarboxylic acid and the lithium-containing compound is strong, the polycarboxylic acid tends to orient and coat the lithium-containing compound rather than randomly coating the surface of the material. This solves the problem of slurry processing stability and avoids the reduction in the specific capacity of the material due to the excessive thickness of the carbon coating layer, and ensures that the negative electrode material after carbonization exhibits 0.4>a>b, and not only has a high initial efficiency but also has good slurry processability.
[0063] The following are detailed steps of the manufacturing method of the embodiments of the present application. S100, prelithiated a silicon-oxygen raw material to obtain a prelithiated material, and the mass ratio of lithium element to silicon-oxygen raw material is (0.02-0.16):1.
[0064] In some embodiments, the silicon oxygen source is a silicate, SiO y 0 <y≦2である。SiO y SiO 0.2 , SiO 0.5 , SiO 0.8 , SiO, SiO 1.2 , SiO 1.5 , SiO 1.8 or SiO 2 etc., and of course, other values within the above range may be used, and the present application is not limited thereto. In this process, the SiO y The skeleton is Li 2 SiO 3 , Li 2 S 2 O 5 etc., improving the first coulombic efficiency of the material.
[0065] In some embodiments, the silicon-oxygen raw material is a silicon-oxygen material having a coating layer, and the prelithiation is performed using the silicon-oxygen material having a coating layer, which makes the prelithiation reaction process milder and is favorable for the uniform distribution of lithium element in the core.
[0066] In some embodiments, when the silicon-oxygen source is a silicon-oxygen material having a covering layer, S100: provide a silicon-oxygen material, mix the silicon-oxygen material with the covering layer, and perform a third heat treatment to form a SiO y / Obtain a coating layer, i.e., a silicon-oxygen material having a coating layer, SiO y / The coating layer is subjected to a prelithiation treatment to obtain a prelithiated material.
[0067] In some embodiments, the mass ratio of silicon-oxygen material to coating material is 1:(0.005-0.05). For example, it may be 1:0.005, 1:0.008, 1:0.01, 1:0.02, 1:0.03, 1:0.04 or 1:0.05, etc., and of course, it may be other values within the above range, and the present application is not limited thereto. Within the above limited range, it can not only ensure that silicon-oxygen material is effectively coated, but also avoid the reduction of the specific capacity of the negative electrode material due to the presence of the coating material.
[0068] In some embodiments, the coating material includes at least one of a carbon material, a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide. The coating material includes a lithium-containing compound, such as Li 2 SiO 3 , Li 2 S 2 O 5 etc., and can be anchored to the material surface, and can also act to shield and reduce the exposure of the lithium-containing compound on the material surface. In addition, the above-mentioned coating material has good thermal conductivity and ionic conductivity, and can improve the heat distribution during the prelithiation reaction process, promote the uniform insertion of lithium ions into the surface of the silicon-oxygen material, and can make the prelithiation reaction proceed uniformly and gently.
[0069] In some embodiments, the temperature of the third heat treatment is 500° C. to 1000° C. For example, it may be 500° C., 600° C., 700° C., 800° C., 900° C., or 1000° C., etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0070] In some embodiments, the time of the third heat treatment is 1h to 6h. For example, it may be 1h, 2h, 3h, 4h, 5h or 6h, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0071] As can be understood, the manufacturing method of coating the silicon-oxygen raw material can be omitted, and the silicon-oxygen material with the coating layer can be directly purchased from the market.
[0072] In some embodiments, prelithiating the silicon oxygen material includes combining the silicon oxygen feedstock with a lithium source followed by a fourth heat treatment to obtain the prelithiated material.
[0073] In some embodiments, the lithium source includes at least one of lithium metal, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride, and lithium aluminum hydride.
[0074] In some embodiments, the mass ratio of silicon oxygen raw material to lithium source is 100: (2 to 16). Specifically, it may be 100: 2, 100: 3, 100: 5, 100: 8, 100: 10, 100: 12, 100: 14, or 100: 16, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0075] In some embodiments, the temperature of the fourth heat treatment is 100° C. to 900° C. For example, the reaction temperature may be 100° C., 200° C., 300° C., 400° C., 500° C., 600° C., 700° C., 800° C., or 900° C., etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0076] In some embodiments, the time of the fourth heat treatment is 1h to 24h. Specifically, it may be 1h, 3h, 5h, 8h, 10h, 13h, 15h, 18h, 20h, or 24h, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0077] S200, a first heat treatment is performed on the mixture including the prelithiated material and the polycarboxylic acid to harden the mixture and obtain a precursor.
[0078] In some embodiments, the prelithiated material and the polycarboxylic acid are mixed to obtain a mixture comprising the prelithiated material and the polycarboxylic acid.
[0079] In some embodiments, the polycarboxylic acid includes at least one of citric acid, tartaric acid, maleic acid, trimesic acid, terephthalic acid, malic acid, and ethylenediaminetetraacetic acid. The polycarboxylic acid has a strong complexing ability, and the polycarboxylic acid can be tightly bonded with the lithium-containing compound exposed on the surface of the silicon oxygen raw material, and the polycarboxylic acid-derived carbon coating layer that forms the "fixed point" is filled in the voids of the surface coating layer of the silicon oxygen raw material. Then, in the carbonization process, a dense carbon layer is formed, which can well shield the lithium-containing compound on the surface of the silicon oxygen raw material containing the lithium element. Due to the shielding effect of the polycarboxylic acid-derived carbon, the second region of the negative electrode material has a Li / O element ratio lower than that of the inside of the negative electrode material, which shows 0.4>a>b. That is, the relative content of lithium element in the surface layer of the negative electrode material of the present application is low, that is, the lithium element is mainly present in the first region of the negative electrode material, which can effectively prevent the intrusion and penetration of the water molecules of the solvent in the process of making the slurry of the negative electrode material. This is advantageous in that it is possible to avoid erosion of silicon crystal grains inside the negative electrode material and generation of gas, and to apply the slurry to the current collector uniformly and evenly, so that the negative electrode can exhibit better electrochemical properties.
[0080] The polycarboxylic acid is a polycarboxylic acid containing two or more carboxylic acid functional groups, and includes at least one of citric acid, tartaric acid, maleic acid, trimesic acid, terephthalic acid, malic acid, and ethylenediaminetetraacetic acid. The polycarboxylic acid has a strong complex forming ability and can be used to form complexes with Li. +and can strongly interact with the lithium-containing compounds on the surface of the prelithiated material, and then undergo carbonization to produce polycarboxylic acid-derived carbon, which can fill the voids and completely cover the lithium-containing compounds on the surface of the material, thereby improving the hydrophobicity of the material and effectively blocking the contact between the Si crystal grains inside the material and the water solvent, and solving the problem of slurry processing stability.
[0081] In some embodiments, the polycarboxylic acid is mixed with a solvent, i.e., the polycarboxylic acid is put into a solvent to obtain a carbon source solution containing the polycarboxylic acid, and the prelithiated material is mixed with the carbon source solution to obtain a mixture containing the prelithiated material and the polycarboxylic acid, and the mixture is first heat-treated to harden it, and then washed to obtain a precursor.
[0082] In some embodiments, the concentration of the carbon source solution is 3 mg / mL to 7 mg / mL. Specifically, it may be 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0083] In some embodiments, the mass ratio of the prelithiated material and the polycarboxylic acid is (20-200): 1. Specifically, the mass ratio of the prelithiated material and the polycarboxylic acid may be 20: 1, 50: 1, 80: 1, 100: 1, 120: 1, 150: 1, 180: 1, or 200: 1, etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0084] The present application can ensure the effect of carbon coating by controlling the concentration of the carbon source solution and the mass ratio of the prelithiated material to the polycarboxylic acid.
[0085] In some embodiments, the solvent comprises at least one of acetone, water, ethanol, methanol, isopropanol, dimethylformamide, toluene, and tetrahydrofuran.
[0086] In some embodiments, the method further comprises drying the mixture before subjecting the mixed material to the first heat treatment.
[0087] In some embodiments, the temperature of the drying treatment is 45° C. to 90° C. Specifically, it may be 45° C., 55° C., 65° C., 70° C., 80° C., 85° C., or 90° C., and of course, it may be other values within the above range, and the present application is not limited thereto. In the actual operation process, the prelithiated material and the carbon source solution are mixed, stirred under heating conditions, evaporated to dryness, and components such as the solvent are removed, and only the polyvalent carboxylic acid and the prelithiated material are retained.
[0088] In some embodiments, the temperature of the first heat treatment is 150°C to 250°C. Specifically, the temperature of the heat curing treatment may be 150°C, 180°C, 200°C, 230°C, or 250°C, etc., and of course, may be other values within the above range, and the present application is not limited thereto. Within the above temperature limit range, the mixture of the prelithiated material and the polycarboxylic acid can be partially carbonized to form a polycarboxylic acid cured layer, and the subsequent washing can remove the soluble lithium-containing compound remaining on the material surface, thereby achieving the purpose of pre-forming. As can be seen, the washing can remove the soluble lithium-containing compound remaining on the material surface to form certain voids on the material surface.
[0089] In some embodiments, the time of the first heat treatment is 5h to 12h, and the specific treatment time may be 5h, 8h, 10h, or 12h, etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0090] In some embodiments, the first heat treatment may be performed in, but is not limited to, an air atmosphere.
[0091] The present application forms a pre-hardened layer by controlling the temperature and time of the first heat treatment, and avoids the influence of subsequent washing on the coating of the carbon source.
[0092] In some embodiments, after the first heat treatment, the material obtained by the first heat treatment is subjected to a process of washing, solid-liquid separation, and drying, and the washing process may include removing moisture from the material.
[0093] In some embodiments, the washed solvent comprises at least one of water and ethanol.
[0094] In some embodiments, the washed liquid-solid mass ratio is (1-4): 1. The specific liquid-solid mass ratio may be 1:1, 2:1, 3:1, or 4:1, etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0095] In some embodiments, the cleaning time is 1h to 5h, and the water washing time may be 1h, 2h, 3h, 4h or 5h, etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0096] In the present application, the lithium-containing compound remaining on the material surface is sufficiently removed by controlling the liquid-solid mass ratio and the cleaning time.
[0097] In some embodiments, the temperature of the drying treatment is 80° C. to 120° C. Specifically, it may be 80° C., 90° C., 100° C., 110° C., 120° C., etc., and of course, it may be other values within the above range, and the present application is not limited thereto.
[0098] In step S300, the precursor is subjected to a second heat treatment to carbonize the precursor and obtain a negative electrode material.
[0099] In some embodiments, the second heat treatment temperature is 500° C. to 800° C. Specifically, the second heat treatment temperature may be 500° C., 600° C., 700° C., or 800° C., etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0100] In some embodiments, the second heat treatment time is 5h to 12h. Specifically, the second heat treatment time may be 5h, 7h, 9h, 11h, or 12h, etc., and of course, may be other values within the above range, and the present application is not limited thereto.
[0101] In this process, during the high-temperature carbonization process of the second heat treatment, the voids on the surface of the polyvalent carboxylic acid cured layer are gradually reduced and closed, and finally a void-free carbon coating layer is formed, and the content of the lithium-containing compound exposed on the surface of the product is reduced. The present invention reduces the porosity of the material surface by controlling the temperature and time of the heat treatment, and forms a dense coating layer that is substantially void-free.
[0102] In some embodiments, the second heat treatment is performed in a protective gas atmosphere, which may be an inert gas such as argon.
[0103] In some embodiments, when the material of the coating layer of the silicon-oxygen material having a coating layer is a carbon material, the coating layer in the produced negative electrode material is a carbon layer, and when the material of the coating layer of the silicon-oxygen material having a coating layer includes at least one of a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide, the produced negative electrode material includes two composite coating layers.
[0104] As described above, in the manufacturing method of the present application, the polycarboxylic acid has a strong complex forming ability and can strongly interact with lithium ions. When the polycarboxylic acid and the silicon-oxygen raw material containing lithium element are mixed in a solution, the polycarboxylic acid tends to be tightly bonded with the lithium-containing compound exposed on the surface of the material, and the polycarboxylic acid-derived carbon coating layer that forms a "fixed point" is filled into the voids of the carbon layer on the surface of the material, and the polycarboxylic acid coating layer is partially carbonized to form a preliminary hardened layer by the first heat treatment. A small amount of lithium-containing compound is embedded in the surface of the polycarboxylic acid hardened layer. The lithium-containing compound remaining on the surface of the polycarboxylic acid hardened layer is removed by the subsequent water washing process, leaving a small amount of voids. In the high-temperature carbonization process, the voids on the surface of the polycarboxylic acid hardened layer are gradually reduced and closed, and finally a void-free carbon coating layer is formed, and the content of the lithium-containing compound exposed on the surface of the product is reduced.
[0105] Embodiments of the present invention further provide a lithium ion battery including the above-described negative electrode material or a negative electrode material produced by the above-described method of production.
[0106] The features and performance of the present invention will be described in more detail below with reference to examples.
[0107] Example 1 This embodiment provides a method for producing a negative electrode material, which is produced by the following method. (1) 1 kg of carbon-coated silicon-oxygen material SiO / C is reacted with 100 g of metallic lithium at a reaction temperature of 500°C for 3 h to obtain a prelithiated carbon-coated silicon-oxygen material Li-SiO / C with a lithium content of 10 wt%. (2) 100 g of Li-SiO / C and 1 g of citric acid were dispersed in 200 mL of acetone, stirred at 45°C, and evaporated to dryness. (3) The evaporated solid was subjected to a heat curing treatment in an air atmosphere at a temperature of 200°C for 12 hours. (4) 100 g of the thermoset product was dispersed in 200 mL of water, stirred at room temperature for 3 hours, filtered by suction, and dried at 100°C. (5) The dried product was carbonized with Ar gas, the heating rate was controlled at 1°C / min, the carbonization temperature was controlled at 500°C, and the carbonization time was controlled at 12 hours. After natural cooling, the product was dispersed and sieved to obtain the final product.
[0108] In addition, as shown in Figure 1, the negative electrode material produced in this example has a bottom layer of prelithium SiO, the inside of the dashed line is the original carbon layer of the raw carbon-coated silicon-oxygen material, and the carbon coating layer outside the dashed line is a dense outer layer formed of a polycarboxylic acid carbon source. The lithium-containing compound is mainly present within the range of the original carbon layer of the raw carbon-coated silicon-oxygen material, and the content of the lithium-containing compound in the dense outer coating layer is small.
[0109] Example 2 The only differences from the first embodiment are as follows. In step (2), 200 g of Li-SiO / C and 1 g of citric acid were dispersed in 200 mL of acetone, stirred at 45° C., and evaporated to dryness. (3) The evaporated solid was subjected to a heat curing treatment in an air atmosphere at a temperature of 250°C for 5 hours.
[0110] Example 3 The only differences from the first embodiment are as follows. (2) 50 g of Li-SiO / C and 1 g of citric acid were dispersed in 200 mL of acetone, stirred at 45°C, and evaporated to dryness. (3) The evaporated solid was subjected to a heat curing treatment in an air atmosphere at a temperature of 150°C for 12 hours.
[0111] Example 4 The only difference from Example 1 is the carbonization conditions. In step (5), the carbonization temperature was 800° C. and the carbonization time was 5 hours.
[0112] Example 5 The main difference from Example 1 is that citric acid in step (2) is replaced with an equal amount of ethylenediaminetetraacetic acid.
[0113] Example 6 The main difference from Example 1 is that citric acid in step (2) is replaced with an equal amount of tartaric acid.
[0114] Example 7 The main difference from Example 1 is the lithium content of the product of step (1). Specifically, (1) 1 kg of carbon-coated silicon-oxygen material SiO / C is reacted with 50 g of metallic lithium at a reaction temperature of 500°C for 3 h to obtain a prelithiated carbon-coated silicon-oxygen material Li-SiO / C with a lithium content of 5 wt%.
[0115] Example 8 The main difference from Example 1 is the lithium content of the product of step (1). Specifically, 1 kg of carbon-coated silicon-oxygen material SiO / C was reacted with 120 g of metallic lithium at a reaction temperature of 500°C for 3 h to obtain a prelithiated carbon-coated silicon-oxygen material Li-SiO / C with a lithium content of 12 wt%.
[0116] Example 9 The main difference from Example 1 is that the silicon-oxygen material precursor in step (1) is different. Specifically, (1) 1 kg of aluminum phosphate-coated silicon-oxygen material SiO / C-AlPO4 was reacted with 100 g of metallic lithium at a reaction temperature of 500°C for 3 h to obtain a prelithiated carbon-coated silicon-oxygen material Li-SiO / C-AlPO 4 The lithium content is 10 wt%.
[0117] Example 10 The main difference from Example 1 is that the silicon-oxygen material precursor in step (1) is different. Specifically, Phosphorus oxide / carbon composite coated silicon oxide material SiO / CP 2 O 5The prelithiated carbon-coated silicon-oxygen material Li-SiO / CP was reacted with 100 g of metallic lithium at a reaction temperature of 500° C. for 3 h. 2 O 5 The lithium content is 10 wt%.
[0118] Example 11 The main difference from Example 3 is the lithium content of the product of step (1). Specifically, 1 kg of carbon-coated silicon-oxygen material SiO / C was reacted with 50 g of metallic lithium at a reaction temperature of 500°C for 3 h to obtain a prelithiated carbon-coated silicon-oxygen material Li-SiO / C with a lithium content of 5 wt%.
[0119] Comparative Example 1 (1) 1 kg of carbon-coated silicon-oxygen material SiO / C is reacted with 100 g of metallic lithium at a reaction temperature of 500°C for 3 h to obtain a prelithiated carbon-coated silicon-oxygen material Li-SiO / C with a lithium content of 10 wt%. In Comparative Example 1, only the step (1) of Example 1 was carried out.
[0120] Comparative Example 2 Comparative Example 2 is a prelithiated carbon-coated silicon-oxygen material Li-SiO / C prepared by a conventional method, in which the lithium content is 5 wt% by reacting the carbon-coated silicon-oxygen material SiO / C with metallic lithium. In Comparative Example 2, only the step (1) of Example 7 was carried out.
[0121] Comparative Example 3 The main difference from Example 1 is that citric acid was replaced with an equal amount of pitch. The process was specifically as follows: 100 g of Li-SiO / C and 1 g of pitch were dispersed in 200 mL of toluene, stirred at 100° C., and evaporated to dryness.
[0122] Comparative Example 4 The only difference from Example 1 is that steps (3) and (4) were not performed.
[0123] Test Example 1 As shown in Tables 1 and 2, the characteristic parameters and electrochemical characteristics of the negative electrode active materials obtained in Examples 1-11 and Comparative Examples 1-4 were measured.
[0124] Test method: The silicon-oxygen composite negative electrode materials obtained in Examples 1-11 and Comparative Examples 1-4 were used as the negative electrode active materials, and the active material: sodium carboxymethylcellulose (CMC): styrene butadiene rubber (SBR) were mixed uniformly in a mass ratio of 96.5:1.5:2, and then coated on a copper foil current collector. After drying, a negative electrode piece was obtained and used as described below. First, a button battery measurement was performed on the obtained electrode piece, and the battery was assembled in an argon glove box, and the measurement was performed using a metallic lithium sheet as the negative electrode and LiPF 6 The electrolyte was 1 mol / L + ethylene carbonate (EC) + methyl ethyl carbonate (EMC), the separator was a polyethylene / propylene composite microporous membrane, and the electrochemical performance was measured using a battery measuring device. The battery capacity was set to the standard 480 mAh / g, the charge / discharge voltage was 0.01 to 1.5 V, and the charge / discharge rate was 0.1 C.
[0125] Measurement of gas generation rate of slurry: After the preparation of the slurry was completed, 20 g of the slurry was weighed and sealed in an aluminum plastic film, and then stored at room temperature for 72 hours. The volume change of the aluminum plastic film before and after storage was measured using a drainage method to obtain the gas generation rate of the slurry.
[0126] Slurry stability measurement: After the slurry preparation is completed, 500g of the slurry is weighed and placed in a beaker, and after storing it at room temperature for 72 hours, it is observed whether or not there is a floating blue color on the surface of the slurry. If a floating blue color is observed, it indicates that the styrene butadiene rubber (SBR) cannot be uniformly dispersed in the slurry, delamination occurs, and the slurry stability is poor.
[0127] [Table 1]
[0128] [Table 2]
[0129] From the data in Tables 1 and 2, the negative electrode material of the present application includes a core and a coating layer, the core includes a silicon-oxygen material, and the negative electrode material includes lithium element. When the mass ratio of lithium element to oxygen element in the negative electrode material is a, and when the negative electrode material is measured by an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the mass ratio of lithium element to oxygen element in the region corresponding to the information that can be detected by the photoelectron spectrometer in the process of detecting from the surface of the negative electrode material to the central region inside the negative electrode material is b, 0.4>a>b is satisfied. It shows that the relative content of lithium element in the surface layer of the negative electrode material of the present application is low, that is, the lithium element is mainly present in the region (i.e., the first region) that cannot be detected by the X-ray photoelectron spectrometer relative to the inside of the negative electrode material particles, which effectively reduces the water solvent molecules from entering the inside of the negative electrode material during the processing and slurry preparation of the negative electrode material, reduces the erosion of the silicon crystal grains of the negative electrode material, improves the stability of the negative electrode material in the slurry processing process, and improves the overall electrochemical properties of the material. In addition, as can be seen from Table 1, the outermost surface of the negative electrode material prepared in the examples was substantially void-free, with almost no gas generation, and the dense carbon layer of the outermost layer effectively blocked contact between the silicon crystal grains inside the material and the aqueous solvent, thereby resolving the problem of slurry processing stability.
[0130] In Comparative Example 1 and Comparative Example 2, the negative electrode material is prepared by prelithiation using only the silicon-oxygen raw material having a coating layer. The surface of the negative electrode material contains a large amount of lithium element, and a>b is not satisfied. Therefore, during the processing and slurry preparation process of the negative electrode material, the water solvent molecules are easily introduced into the negative electrode material, the silicon crystal grains are eroded, and the stability of the negative electrode material is affected. As a result, the specific capacity, initial coulombic efficiency and cycle stability of the negative electrode material are all poor.
[0131] In Comparative Example 3, when pitch is used to coat the pre-lithiated material, the pitch cannot bond closely with the lithium-containing compound exposed on the surface of the material, so that the material has many voids, a large amount of gas is generated, and the lithium element contained in the surface of the material is large, and a>b is not satisfied. As a result, during the processing and slurry preparation of the negative electrode material, water solvent molecules are easily introduced into the negative electrode material, eroding the silicon crystal grains and affecting the stability of the negative electrode material, and the specific capacity, initial coulombic efficiency, and cycle stability of the negative electrode material are all poor.
[0132] In Comparative Example 4, polycarboxylic acid is used for coating, and then carbonized directly. In the initial decomposition process of polycarboxylic acid, voids are generated, which again expose part of lithium-containing compound, that is, part of lithium-containing compound is still not completely coated, and forms mosaic structure. In the later carbonization process of this mosaic structure, which is reserved, that is, lithium-containing compound is still exposed, and the material does not satisfy a>b, which affects the stability of negative electrode material, and the specific capacity, initial coulombic efficiency and cycle stability of negative electrode material are all poor.
[0133] The above is merely a preferred embodiment of the present invention, and is not intended to limit the present invention. Those skilled in the art can make various modifications and changes to the present invention. Any modifications, equivalent replacements, improvements, etc. made within the scope of the spirit and principle of the present invention should be included in the protection scope of this application. [Explanation of symbols]
[0134] In Figure 1 100-core 200-Lithium element 300-Covering layer 301-1st coating layer 302-Second coating layer 1-First area 2-Second area
Claims
1. A negative electrode material comprising a core and a coating layer located on at least a portion of a surface of the core, the core comprises a silicon-oxygen material, and the negative electrode material comprises a lithium element; a mass ratio of lithium element to oxygen element in the negative electrode material is a, and a mass ratio of lithium element to oxygen element in a region corresponding to information detectable in a process in which the negative electrode material is measured by an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha) from the surface of the negative electrode material toward a central region inside the negative electrode material is b, the relationship between a and b satisfies 0.4>a>b.
2. The negative electrode material according to claim 1, characterized in that it has at least one of the following characteristics (1) to (7). (1) the mass ratio (a) of lithium element to oxygen element in the negative electrode material satisfies 0.35>a>0.15; (2) b satisfies 0.30>b>0.01; (3) When the negative electrode material is measured using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha), the thickness of the region corresponding to information detectable by the photoelectron spectrometer in the process of detecting from the surface of the negative electrode material toward the central region inside the negative electrode material is 1 nm to 10 nm; (4) The silicon-oxygen material is silicon oxide (SiO x (0<x≦2) (5) The silicon-oxygen material is Li 2 SiO 3 , Li 2 S 2 O 5 and Li 4 SiO 4 The lithium-containing compound includes at least one of the following: (6) When the mass of the negative electrode material is 100%, the mass ratio of the lithium element in the negative electrode material is 1 wt % to 15 wt %; (7) The molar ratio of Si element to O element in the negative electrode material is (0.8-1.2):
1.
3. The negative electrode material according to claim 1, characterized in that the coating layer includes a first coating layer and a second coating layer, and the second coating layer is located between the core and the first coating layer and / or in an area on the surface of the core that is not covered by the first coating layer.
4. The negative electrode material according to claim 3, characterized in that it has at least one of the following characteristics (1) to (6). (1) The second coating layer includes at least one of a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide; (2) The material of the first coating layer includes a carbon material; (3) The mass ratio of the first coating layer in the negative electrode material is 0.1% to 5%; (4) The mass ratio of the second coating layer in the negative electrode material is 0.1% to 8%; (5) the thickness of the first coating layer is 1 nm to 1000 nm; (6) The second coating layer has a thickness of 1 nm to 1000 nm.
5. The negative electrode material according to claim 1, characterized in that it has at least one of the following characteristics (1) to (2). (1) The coating layer is a carbon layer; (2) The thickness of the coating layer is 1 nm to 1000 nm.
6. The negative electrode material according to claim 1, characterized in that it has at least one of the following characteristics (1) to (5). (1) The pore volume of the negative electrode material is less than 0.01 cm 3 / g or less; (2) The specific surface area of the negative electrode material is 4 m 2 / g or less; (3) The contact angle θ of the negative electrode material with acetone measured by the Washburn method is θ>20°; (4) The pH of the negative electrode material satisfies 7<pH<11.5; (5) The median diameter of the negative electrode material is 3.0 μm to 10.0 μm.
7. A step of prelithiating a silicon-oxygen raw material to obtain a prelithiated material containing lithium element and silicon-oxygen raw material in a mass ratio of (0.02-0.16):1; performing a first heat treatment on the mixture including the prelithiated material and a polycarboxylic acid to harden the mixture and obtain a precursor; and performing a second heat treatment on the precursor to carbonize the precursor and obtain a negative electrode material.
8. The method according to claim 7, characterized in that it has at least one of the following characteristics (1) to (13): (1) The temperature of the first heat treatment is 150° C. to 250° C.; (2) The time of the first heat treatment is 5 h to 12 h; (3) The first heat treatment is performed in an air atmosphere; (4) before subjecting the mixture containing the prelithiated material and the polycarboxylic acid to a first heat treatment, the mixture containing the prelithiated material and the polycarboxylic acid is further subjected to a drying treatment; (5) Before subjecting the mixture containing the prelithiated material and the polycarboxylic acid to a first heat treatment, the mixture containing the prelithiated material and the polycarboxylic acid is further subjected to a drying treatment, and the temperature of the drying treatment is 45° C. to 90° C.; (6) performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into a solid-liquid mixture, and drying the material, and then obtaining a precursor; (7) A process for performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into solid and liquid, and drying the material, wherein a solvent used for the washing includes at least one of water and ethanol; (8) A process for performing a first heat treatment on the mixture containing the prelithiated material and a polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment, and drying the material, wherein the solid-liquid mass ratio during the washing is (1 to 4):1; (9) performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into solid and liquid, and drying the material, the washing time being 1h to 5h; (10) A process for performing a first heat treatment on the mixture containing the prelithiated material and the polycarboxylic acid, and then washing, separating the material obtained by the first heat treatment into solid and liquid, and drying the material, the drying temperature being 80° C. to 120° C.; (11) The temperature of the second heat treatment is 500° C. to 800° C.; (12) The time of the second heat treatment is 5h to 12h; (13) The second heat treatment is performed in a protective gas atmosphere.
9. The method for producing the mixture containing the prelithiated material and the polycarboxylic acid according to claim 7, comprising: adding the polycarboxylic acid to a solvent to obtain a carbon source solution containing the polycarboxylic acid; and mixing the prelithiated material with the carbon source solution containing the polycarboxylic acid to obtain a mixture containing the prelithiated material and the polycarboxylic acid.
10. The method according to claim 9, characterized in that it has at least one of the following characteristics (1) to (4). (1) The concentration of the carbon source solution is 3 mg / mL to 7 mg / mL; (2) The polycarboxylic acid includes at least one of citric acid, tartaric acid, maleic acid, trimesic acid, terephthalic acid, malic acid, and ethylenediaminetetraacetic acid; (3) the solvent comprises at least one of acetone, water, ethanol, methanol, isopropanol, dimethylformamide, toluene, and tetrahydrofuran; (4) The mass ratio of the prelithiated material to the polycarboxylic acid is (20 to 200):
1.
11. 8. The method according to claim 7, wherein the silicon oxygen raw material is a silicon oxygen material having a covering layer, and the method for producing the silicon oxygen material having a covering layer includes providing a silicon oxygen material, mixing the silicon oxygen material with a covering material, and then performing a third heat treatment to obtain a silicon oxygen material having a covering layer.
12. The method according to claim 11, characterized in that it has at least one of the following characteristics (1) to (4). (1) the mass ratio of the silicon-oxygen material to the coating material is 1:(0.005-0.05); (2) The coating material includes at least one of a carbon material, a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum phosphorus composite oxide; (3) the temperature of the third heat treatment is 500° C. to 1000° C.; (4) The time for the third heat treatment is 1 hour to 6 hours.
13. 8. The method of claim 7, wherein the step of prelithiating the silicon-oxygen feedstock includes mixing the silicon-oxygen feedstock with a lithium source and then performing a fourth heat treatment to obtain a prelithiated material.
14. The method according to claim 13, characterized in that it has at least one of the following characteristics (1) to (7): (1) The silicon-oxygen source is SiO y (0<y≦2); (2) the lithium source comprises at least one of metallic lithium, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride, and lithium aluminum hydride; (3) the mass ratio of the silicon oxygen source to the lithium source is 100:(2-16); (4) The temperature of the fourth heat treatment is 100° C. to 900° C.; (5) The time of the fourth heat treatment is 1 h to 24 h; (6) The silicon-oxygen source is a silicon-oxygen material having a covering layer; (7) The silicon / oxygen raw material is a silicon / oxygen material having a coating layer, and the material of the coating layer includes at least one of a carbon material, a silicon phosphate compound, an aluminum phosphate compound, an ammonium phosphate compound, and an aluminum / phosphorus composite oxide.
15. A lithium ion battery comprising the negative electrode material according to any one of claims 1 to 6 or the negative electrode material produced by the method for producing the negative electrode material according to any one of claims 7 to 14.
Citation Information
Patent Citations
Lithium battery anode material with lithium content in gradient distribution, and preparation method thereof and lithium battery
CN111554911A
Pre-lithiated silicon-oxygen composite material, negative pole piece, lithium battery and preparation method of composite material
CN112701267A
Powder for negative electrode of lithium ion secondary battery, and method of manufacturing the same
JP2015153520A